“Pre-referral process about learning disabilities in students of "Poalò- García Moreno" educational unit: perceptions of English teachers in efl” - Chugchilán Alvarado, Dayra Evelyn (2023)
The present study focused on analyzing the perspectives of the teachers of “Poaló-García Moreno” Educational Unit regarding the problems and learning disabilities in their students. The objective of the research was to identify teachers’ perceptions of how they recognize and address learning disabilities in the classroom. To achieve this objective, a qualitative and descriptive methodology was used. Interviews were carried out with a group of teachers from the educational establishment, which allowed obtaining detailed and rich information about their points of view and experiences in relation to the subject. Through these interviews, valuable information was gathered about the strategies they use to identify learning disabilities, how they support students, and the challenges they face in the process. The relevant results of the research revealed that the teachers of the “Poaló-García Moreno” Educational Unit use different approaches to identify learning disabilities in their students. Some emphasized classroom observation and constant monitoring of academic performance, while others stressed the importance of establishing effective communication with other professionals and parents to obtain a more complete picture of student performance. In addition, it was found that teachers consider it essential to have the support of experts in LD for accurate identification and effective intervention. Collaboration with specialists in this area allows them to design personalized and appropriate intervention plans for each student, which improves the educational experience and academic performance of those who face learning disabilities. The research highlighted the importance of early detection of learning disabilities, which makes it possible to provide the necessary support from the early stages of education and avoid possible delays in academic development. The study showed the different perspectives of teachers in relation to the problems and learning disabilities of their students. The results underscored the importance of collaboration with experts in learning disabilities and early, personalized intervention to improve the educational experience and academic achievement of students.